Pemberian Cookies Tepung Ikan Lele dan Tepung Mocaf terhadap Perubahan Berat Badan Balita Gizi Kurang - Ramadhani, Ni Shafa Khalishah Salsabila; Sartono, Sartono; Hartati, Yuli (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2023)
Background: Malnutrition is a state of health problems that occurs when the body lacks of nutrients needed for development, thinking, and other life activities. The growth process that inhibits the lack of energy that causes the body to become weak and the immune system weakens, which will facilitate the spread of disease, as well as decreased mental development resulting in weak thinking skills and permanent disruption of brain function are the result of nutritional problems in toddlers. Purpose : The purpose of this study was to determine the effect of giving catfish flour cookies and mocaf flour to changes in the body weight of nourished children under five. Methods: The type of this research is a true experiment (pure experiment) with a pre-test and post-test design with a control group. Results: The results of the independent t-statistical test the difference in the average weight difference of children under five in the treatment group increased by 337.50 g and in the control group increased by 187.50 grams with p-value = 0.000. Conclusion: Cookies of catfish flour and mocaf flour affect changes in the body weight of undernourished toddlers and can be used as alternative food additives.